Efeitos de uma intervenção de gestão de casos sobre os fatores de risco neuropsicológicos em pessoas idosas caidoras da comunidade: ensaio clínico randomizado - Florido, João Vitor Businaro (Universidade Federal de São Carlos, 2022)
Introduction: Falls are directly related to morbidity and mortality in older people. Multifactorial and individualized approaches based on risk factors for falls are needed. Objective: To verify the effects of an intervention based on case management on neuropsychological factors in community-dwelling faller older people. Method: A single-blind randomized clinical trial conducted, with 55 participants over 60 years old, and with a history of at least two falls in the last year. The assessment took place in three moments, before intervention, after 16 weeks of intervention and short follow up after 6 weeks. Assessors blinded to the intervention collected anamnesis data and neuropsychological factors (Addenbrooke Cognitive Examination - Revised version, Mini Mental State Examination, Verbal Fluency Test, Geriatric Depression Scale, Falls Efficacy Scale-International and Geriatric Anxiety Inventory). The Control Group (n=26) was monitored for falls management and health conditions. The Intervention Group (n=29) was conducted to a case management for fallers, lasting 16 weeks, once a week. The intervention included a multidimensional assessment of risk factors for falls, discussion about the identified risk factors, preparation of an individualized intervention plan with the participant, application, monitoring and review of the plan. For analyzes, a significance level of α = 0.05 was adopted and the SPSS software (22.0) was used to perform the statistical tests. The analysis was carried out by intention to treat. Results: After 16 weeks, 55 volunteers were re-assessed, with a loss of 5 participants at 6-week follow-up. There was a non-significant trend of difference between groups after 6 weeks of follow-up in ACE-R visuospatial domain, with lower values in the CG. There were no significant differences between groups or between estimates in other variables, risk of depression and anxiety and fear of falling. Both groups showed a non-significant increase in the ACE-R assessment, especially the GI, from a non-significant decrease in the FES-I assessment in groups. Conclusion: Intervention based on case management has the potential to improve or maintain neuropsychological factors in community-dwelling faller older people. However, more clinical trials are needed to prove its effects.
Effects of a case management intervention on neuropsychological risk factors in community-dwelling older adults who fell: a randomized clinical trial
Keywords: Acidentes por quedas; Cognição; Pessoa idosa; Prevenção de quedas; Testes neuropsicológicos; CIENCIAS DA SAUDE::SAUDE COLETIVA::MEDICINA PREVENTIVA